Dimethylamino acid esters as biodegradable and reversible transdermal permeation enhancers: effects of linking chain length, chirality and polyfluorination - Novotný, Jakub; Kovaríková, Petra; Novotný, Michal; Janůsová, Barbora; Hrabálek, Alexandr; Vávrová, Katerina (Pharmaceutical research, 2009)
PURPOSE: Series of N,N-dimethylamino acid esters was synthesized to study their transdermal permeation-enhancing potency, biodegradability and reversibility of action. Effects of chirality, linking chain length and polyfluorination were investigated. MATERIALS AND METHODS: In vitro activities were evaluated using porcine skin and four model drugs-theophylline, hydrocortisone, adefovir and indomethacin. Biodegradability was determined using porcine esterase, reversibility was measured using electrical resistance. RESULTS: No differences in activity were found between (R), (S) and racemic dodecyl 2-(dimethylamino)propanoate (DDAIP). Substitution of hydrocarbon tail by fluorocarbon one resulted in loss of activity. Replacement of branched linking chain between nitrogen and ester of DDAIP by linear one markedly improved penetration-enhancing activity with optimum in 4-6C acid derivatives. Dodecyl 6-(dimethylamino)hexanoate (DDAK) was more potent than clinically used skin absorption enhancer DDAIP for theophylline (enhancement ratio of DDAK and DDAIP was 17.3 and 5.9, respectively), hydrocortisone (43.2 and 11.5) and adefovir (13.6 and 2.8), while DDAIP was better enhancer for indomethacin (8.7 and 22.8). DDAK was rapidly metabolized by porcine esterase, and displayed low acute toxicity. Electrical resistance of DDAK-treated skin barrier promptly recovered to control values. CONCLUSION: DDAK, highly effective, broad-spectrum, biodegradable and reversible transdermal permeation enhancer, is promising candidate for future research.
Keywords: farmaceutická chemie; stabilita léku; Animals; Caproates; hydrolýza; Adenine; halogenace; Halogenation; hydrokortison; indomethacin; Methylamines; Drug Carriers; Molecular Structure; časové faktory; aplikace kožní; Skin Absorption; Indomethacin; Structure-Activity Relationship; theofylin; Chemistry, Pharmaceutical; Hydrocortisone; Time Factors; Administration, Cutaneous; prasata; kůže; Esterases; dimethylaminy; kožní absorpce; Drug Stability; Dimethylamines; isomerie; kapronáty; příprava léků; molekulární struktura; Dodecanol; dodekanol; organofosfonáty; adenin; elektrická impedance; Isomerism; Skin; Swine; methylaminy; Hydrolysis; esterasy; nosiče léků; vztahy mezi strukturou a aktivitou; Drug Compounding; zvířata; alanin; Theophylline; Electric Impedance; Alanine; Organophosphonates